Pengaruh Teaching Factory (TEFA) Terhadap Minat Wirausaha Siswa Tata Busana SMK Negeri 1 Brondong - Rahma Faradiba Nur Eliza; Imami Arum Tri Rahayu (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The purpose of this study is to 1) Analyze the implementation of Teaching Factory on Fashion Production Design students at SMK Negeri 1 Brondong, 2) Analyze the entrepreneurial interest of Fashion Production Design students at SMK Negeri 1 Brondong, 3) Analyze the influence of Teaching Factory on the entrepreneurial interest of Fashion Production Design students at SMK Negeri 1 Brondong. This study is an Ex-Post Facto research type with secondary data using quantitative descriptive methods. The sample in this study was all grade XII Fashion Production Design students at SMK Negeri 1 Brondong obtained using nonprobability sampling techniques with a total sampling method of 11 students. Data collection techniques were carried out through questionnaires and documentation. The results of this study indicate that the implementation of Teaching Factory is in the high category and the interest in entrepreneurship is very high. The results of the Spearman Rank Correlation test obtained a significance value of 0.006 <0.05, so Ha is accepted and H0 is rejected. The correlation coefficient value of 0.761 indicates a strong and positive relationship between Teaching Factory and students' entrepreneurial interest. In addition, the coefficient of determination (R Square) value of 0.516 shows that the influence of Teaching Factory on students' entrepreneurial interest is 51.6%, while 48.4% is influenced by other factors outside of research.